Comparison of device-based physical activity and sedentary behaviour following percutaneous coronary intervention in a cohort from Sweden and Australia: a harmonised, exploratory study - Nicole Freene; Sabina Borg; Margaret McManus; Tarryn Mair; Ren Tan; Rachel Davey; Birgitta Öberg; Maria Bäck (BMC, 2020)
Abstract Background Few studies have measured device-based physical activity and sedentary behaviour following a percutaneous coronary intervention (PCI), with no studies comparing these behaviours between countries using the same methods. The aim of the study was to compare device-based physical activity and sedentary behaviour, using a harmonised approach, following a PCI on-entry into centre-based cardiac rehabilitation in two countries. Methods A cross-sectional study was conducted at two outpatient cardiac rehabilitation centres in Australia and Sweden. Participants were adults following a PCI and commencing cardiac rehabilitation (Australia n = 50, Sweden n = 133). Prior to discharge from hospital, Australian participants received brief physical activity advice (< 5 mins), while Swedish participants received physical activity counselling for 30 min. A triaxial accelerometer (Actigraph GT3X/ActiSleep) was used to objectively assess physical activity (light (LPA), moderate-to-vigorous (MVPA)) and sedentary behaviour. Outcomes included daily minutes of physical activity and sedentary behaviour, and the proportion and distribution of time spent in each behaviour. Results There was no difference in age, gender or relationship status between countries. Swedish (S) participants commenced cardiac rehabilitation later than Australian (A) participants (days post-PCI A 16 vs S 22, p < 0.001). Proportionally, Swedish participants were significantly more physically active and less sedentary than Australian participants (LPA A 27% vs S 30%, p < 0.05; MVPA A 5% vs S 7%, p < 0.01; sedentary behaviour A 68% vs S 63%, p < 0.001). When adjusting for wear-time, Australian participants were doing less MVPA minutes (A 42 vs S 64, p < 0.001) and more sedentary behaviour minutes (A 573 vs S 571, p < 0.001) per day. Both Swedish and Australian participants spent a large part of the day sedentary, accumulating 9.5 h per day in sedentary behaviour. Conclusion Swedish PCI participants when commencing cardiac rehabilitation are more physically active than Australian participants. Potential explanatory factors are differences in post-PCI in-hospital physical activity education between countries and pre-existing physical activity levels. Despite this, sedentary behaviour is high in both countries. Internationally, interventions to address sedentary behaviour are indicated post-PCI, in both the acute setting and cardiac rehabilitation, in addition to traditional physical activity and cardiac rehabilitation recommendations. Trial registrations Australia: Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12615000995572 . Registered 22 September 2015, Sweden: World Health Organization Trial Registration Data Set: NCT02895451 .